Extraction kinetics, thermodynamics, rheological properties and anti-BVDV activity of the hot water assisted extraction of Glycyrrhiza polysaccharide. Issue 5 (24th April 2020) - Wang, Yonggang; Wang, Xinjian; Zhang, Kang; Zhang, Xuan; Li, Shaowei; Li, Yanlin; Fan, Wenguang; Leng, Feifan; Yang, Mingjun; Chen, Jixiang
Abstract : The extraction kinetics and thermodynamic parameters of Glycyrrhiza polysaccharide (GP) were studied, and its rheological properties and antiviral activity were evaluated. Abstract : The extraction kinetics and thermodynamic parameters of Glycyrrhiza polysaccharide (GP) were studied, and its rheological properties and antiviral activity were evaluated. The results showed that the extraction process could be fitted to Fick's second law of diffusion. The optimum concentration (97.62 mg mL −1 ) was obtained at a solid–liquid ratio of 1 : 15, (g mL −1 ), an extraction time of 120 min and an extraction temperature of 80 °C. The whole extraction process was spontaneous and endothermic. GP was shown to be an acid glycoprotein with a complex structure using high performance liquid chromatography (HPLC), circular dichroism (CD) and Fourier-transform infrared spectroscopy (FT-IR). A study of its rheological properties showed that GP has the characteristics of a typical non-Newtonian pseudoplastic fluid and that its viscosity could be significantly affected by temperature, pH and the presence of other ions. Branched and soft fiber structures with irregular molecular aggregation were observed by scanning electron microscopy (SEM) and atomic force microscopy (AFM). Moreover, GP showed good inhibitory activity against bovine viral diarrhea virus (BVDV) via the regulation of the relative expression levels of the IRF-1 and IRF-3 genes in MDBK cells. This activity was found to be dependent on the physicochemical and structural properties of GP. These findings imply that GP can be considered as a natural source of active material for the prevention of viral disease.